Bioprospecting and molecular identification of Streptomyces on karst ecosystems in the coastal area of Gorontalo, Indonesia, as plant growth-promoting rhizobacteria - YULIANA RETNOWATI; ABUBAKAR SIDIK KATILI; NOVRI YOULA KANDOWANGKO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Retnowati Y, Katili AS, Kandowangko NY. 2025. Bioprospecting and molecular identification of Streptomyces on karst ecosystems in the coastal area of Gorontalo, Indonesia, as plant growth-promoting rhizobacteria. Biodiversitas 26: 3294-3301. Agricultural systems that rely on synthetic pesticides, chemical fertilizers, herbicides, and monoculture farming systems contribute to declining soil fertility and affect the soil microbial community. In contrast, organic farming systems incorporate Plant Growth-Promoting Rhizobacteria (PGPR) as a potential solution. Therefore, this study aimed to explore the prospecting of Streptomyces from the rhizosphere of plants in the karst ecosystem PGPR on the coastal area of Gorontalo by using a molecular approach to identify promising strains. The success of this study in isolating and identifying three promising Streptomyces strains is a testament to the robustness of this study. Soil sampling was conducted at three locations at a 15-30 cm depth. The PGPR potential of Streptomyces was determined based on phosphate-solubilizing activity, Indole acetic acid production, antagonism to the root pathogenic fungus, and tolerance to fungicide capability. This study successfully isolated three Streptomyces from Jatropha curcas rhizosphere. In line with these findings, 16S rRNA sequencing showed the affinity of the strain to the genus Streptomyces on 98.39 to 99.65% of homology, including Streptomyces sp. strain KRJc-01, Streptomyces rochei strain KRJc-02, and Streptomyces pratensis strain KRJc-03. The initial in vitro assay showed the potential ability of Streptomyces sp. in phosphate-solubilizing activity, indole acetic acid production, antagonistic against root-pathogenic fungi, and fungicide tolerance capability. Antagonistic activity against the root-pathogenic fungus of Fusarium oxysporum is supported by PKSs and NRPS gene cluster. In general, these findings suggest that Streptomyces sp. from the rhizosphere of plants in the karst ecosystem within Gorontalo has significant potential as PGPR, contributing to sustainable crop improvement.